Thermal analysis of molten ternary lithium-sodium-potassium nitrates. (April 2017) - Mohammad, Mehedi Bin; Brooks, Geoffrey Alan; Rhamdhani, M. Akbar
Abstract: The pre-melting, melting and degradation events of a ternary LiNO3 -NaNO3 -KNO3 (29.63-13.23-57.14 wt%) salt have been investigated using simultaneous thermal analyzer (STA) for potential use as a heat transfer and storage fluid (HTF). This composition was selected based on the thermochemical calculation using the FactSage 7.0 to find the lowest solid-liquid equilibrium temperature. The melting point obtained from STA (122.8 °C) indicated a good agreement with the theoretical value determined by FactSage (120.8 °C), which is 100 °C less compared to binary NaNO3 :KNO3 solar salt. The salt was heated from 50 to 800 °C in 3 atm (argon, air, and O2 ) at three scanning rates (2.5, 5 and 10 °C/min) to investigate its decomposition limits. At 10 °C/min scanning rate the salt started to degrade rapidly at 545 °C in argon, 571 °C in air and 600 °C in oxygen, respectively. In argon at a higher heating rate (10 °C/min), the salt degradation was delayed by 42 °C. The main gaseous products of decomposition were found to be O2, N2, NO, N2 O and NO2 . After melting, at higher temperature the evolution of O2 and NO indicated that primary and secondary decomposition reactions are concurrent and overlapping. The heating-cooling rates have low effect on the onset of melting and offset freezing temperatures but, have an effect on peaks height, peaks width, and transition enthalpies. The α/β transition (75 °C peak temperature) during cooling only appeared at the 1 °C/min cooling rate. The ternary salt offers 70 °C greater operating temperature range compared to binary solar salt in argon. At a higher partial pressure of O2, decomposition was delayed by 55 °C (at 10 °C/min), which could be used to increase the power cycle efficiency of solar electricity generation. Highlights: A low melting point ternary nitrate mixture is proposed as heat transfer fluids. The thermal stability of nitrate is increased in O2 and at higher scanning rate. O2, N2, NO, N2 O and NO2 are the main evolved gaseous products of decomposition.